ANALISIS RASIO PROFITABILITAS TERHADAP PERUBAHAN LABA PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siyamul Fadilah; Rismansyah Rismansyah; Totok Sudiyanto (Universitas Nusa Cendana, 2023)
This study was conducted to test the effect of Profitability Ratios (ROA and ROE) on the Profits Changes of PT. Telkom and PT. Indosat. The research method used is the quantitative method. The results of the hypothesis partially conclude that the Return on Assets (ROA) has no significant effect on Profits Changes and the Return on Equity (ROE) has no significant effect on Profits Changes. Meanwhile, the results of the F test conclude that Return on Assets (ROA) and Return on Equity (ROE) simultaneously affect Profits Changes. For further research, it is suggested to expand the variables that will be used in the research. Keywords: Return on Assets (ROA); Return on Equity (ROE); Profit Changes; Telecommunications Companies